2022
DOI: 10.3390/polym14020307
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Unconfined Compression Strength and Microstructure Characteristics of Slag and Fly Ash-Based Geopolymer Stabilized Riverside Soft Soil

Abstract: To solve the issues of insufficient early strength of cement stabilized soil and high resource cost, high reduction cost, and high environmental cost induced by the application of cement, the slag and fly ash-based geopolymer was adopted as the stabilizer to treat riverside soft soil. This study mainly investigated the effects of stabilizer content, slag-to-fly ash ratio, and alkaline activator content on the strength of geopolymer stabilized soils with different curing ages. Unconfined compressive strength (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Moreover, stable network structure products were uniformly distributed on the surface of the stabilized soil particles. When combined with the XRD results, they were determined to be N-A-S-H gels (typical polymerization products) [ 31 , 32 ]. The N-A-S-H gel contributes to enhancing the bonding strength between soil particles and preventing the intrusion of free sulfate ions into the stabilized soil [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, stable network structure products were uniformly distributed on the surface of the stabilized soil particles. When combined with the XRD results, they were determined to be N-A-S-H gels (typical polymerization products) [ 31 , 32 ]. The N-A-S-H gel contributes to enhancing the bonding strength between soil particles and preventing the intrusion of free sulfate ions into the stabilized soil [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…A cube mold with a side length of 70.7 mm was used for all immersion tests. According to the literature [ 31 ], after the fresh, stabilized soil mixture was molded, it was covered with plastic wrap until demolding after 24 h. The demolded specimens were cured under standard curing conditions for 28 days.…”
Section: Materials and Test Programmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the experimental method in [ 39 ], the 3, 7, and 28 d UCS values of the stabilized soil specimens were tested by a universal testing machine, as shown in Figure 1 .…”
Section: Materials and Test Programmentioning
confidence: 99%
“…Further studies found that lower moisture content and composite geopolymer materials were helpful in reducing poor bonding between the geopolymer and soil particles [ 35 , 36 , 37 , 38 ]. Luo et al [ 39 ] proposed using slag/fly ash composite as a stabilizer for soft soil; the measured 28-day UCS of stabilized soil was higher than that of undisturbed soil (56.0 times higher) and cement-stabilized soil (1.39 times higher). Singhi et al [ 31 ] found that Si/Al and Na/Al ratios were important factors affecting the soil–geopolymer system (the main raw materials of which were fly ash and slag), and different mixing ratio schemes corresponded to different stabilization effects.…”
Section: Introductionmentioning
confidence: 99%